Inheritance Sharing System in Tinombala Village from the Perspective of Islamic Law - M. Taufan B.; Muhammad Yusuf Surya; Nasaruddin Nasaruddin (State Institute for Islamic Studies Palu, 2022)
The legal system in Indonesia is plural in nature of the existence of customary law, Islamic law, and laws in Western traditions. The customary law system seems to be dominantly used by rural communities in solving private problems, such as the distribution of inheritance. Considering Indonesia has a Muslim majority population, this article discusses the inheritance distribution system in rural communities from the perspective of Islamic law. The research location is Tinombala Village in Parigi Mautong Regency. This study uses qualitative methods with three data collection techniques: observation, interviews, and documentation. Primary and secondary data were analyzed using data reduction, presentation, and verification methods. The results of this study indicate that the distribution of inheritance carried out by the villagers is determined based on customary law, even though the majority of the population is Muslim. Based on local customary law, the assets left by the deceased parents are distributed only to the children who died. The last child often gets the most share. Such practice is not following the principle of inheritance distribution in Islamic law.